2012
DOI: 10.1111/j.1365-313x.2012.05053.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant ERD2‐like proteins function as endoplasmic reticulum luminal protein receptors and participate in programmed cell death during innate immunity

Abstract: SUMMARYThe hypersensitive response (HR), a form of programmed cell death (PCD), is a tightly regulated innate immune response in plants that is hypothesized to restrict pathogen growth and disease development. Although considerable efforts have been made to understand HR PCD, it remains unknown whether the retrograde pathway from the Golgi to the endoplasmic reticulum (ER) is involved. Here we provide direct genetic evidence that two Nicotiana benthamiana homologs, ERD2a and ERD2b, function as ER luminal prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 75 publications
1
46
0
1
Order By: Relevance
“…The TBF1 promoter was amplified from the Arabidopsis genomic DNA and flanked with Hind III/ Spe I using primers P14/P15 and ligated into pGX179, which was cut with Hind III/ Xba I, to generate pGX181 ( TBF1p:uorfs TBF1 -Gateway-NOS ). LUC , GFP ER and snc1 were amplified from pGWB235 26 , GFP-HDEL 27 and the snc1 mutant genomic DNA, respectively. TBF1-YFP and NPR1-EGFP were fused together through PCR, cloned via ligation independent cloning 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TBF1 promoter was amplified from the Arabidopsis genomic DNA and flanked with Hind III/ Spe I using primers P14/P15 and ligated into pGX179, which was cut with Hind III/ Xba I, to generate pGX181 ( TBF1p:uorfs TBF1 -Gateway-NOS ). LUC , GFP ER and snc1 were amplified from pGWB235 26 , GFP-HDEL 27 and the snc1 mutant genomic DNA, respectively. TBF1-YFP and NPR1-EGFP were fused together through PCR, cloned via ligation independent cloning 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Xoc strain RH3 was grown on nutrient agar medium (0.1% yeast extract, 0.3% beef extract, 0.5% polypeptone, and 1% sucrose) at 28 °C for 2 d before resuspension in sterile water and dilution to OD 600nm = 0.5 for inoculation. 5 to 10 leaves of each plant were inoculated by the penetration method using a needleless syringe at the tillering stage 27 . Disease was scored by measuring the lesion length at 14 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…We found that ERD2a (GU388433) and ERD2b (GU388432) had the activity of ER luminal protein receptor. 17 By a high-throughput virus-induced gene silencing (VIGS) screen, we found that knocking down ERD2b delayed the nonhost pathogen Xanthomonas oryzae unknown. All the results suggest a conserved role of ERD2 may exist evolutionarily.…”
mentioning
confidence: 99%
“…8 In contrasts, Arabidopsis ERD2a, N. benthamiana ERD2a and ERD2b have been found to function in yeast. 10,17 Further, ERD2a and ERD2b have been proved to function as ER luminal protein receptor in plants. 17 Whether the other five class II ERD2-like proteins in plants can function as ER luminal protein receptor needs to be investigated further.…”
mentioning
confidence: 99%
See 1 more Smart Citation